2018
DOI: 10.1002/jsfa.8953
|View full text |Cite
|
Sign up to set email alerts
|

Healthy and sustainable diets for future generations

Abstract: Global food systems will face unprecedented challenges in the coming years. They will need to meet the nutritional needs of a growing population and feed an expanding demand for proteins. This is against a backdrop of increasing environmental challenges (water resources, climate change, soil health) and the need to improve farming livelihoods. Collaborative efforts by a variety of stakeholders are needed to ensure that future generations have access to healthy and sustainable diets. Food will play an increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 45 publications
0
17
0
Order By: Relevance
“…This study also revealed that bean nutritional quality and yields were reduced under future predicted drought conditions, leading the authors to conclude, with supportive data from crop modeling, that current bean growing areas in south‐eastern Africa could become unsuitable by 2050. Given the predicted impact of future drought conditions on crops and, as 66% of people live with severe water scarcity for at least one month of the year and humans use 70% of available fresh water for agricultural purposes, the monitoring of water irrigation systems is a recommended strategy to help conserve water (Green et al., 2018).…”
Section: Quality Of Food Resources In a Changing Climatementioning
confidence: 99%
See 1 more Smart Citation
“…This study also revealed that bean nutritional quality and yields were reduced under future predicted drought conditions, leading the authors to conclude, with supportive data from crop modeling, that current bean growing areas in south‐eastern Africa could become unsuitable by 2050. Given the predicted impact of future drought conditions on crops and, as 66% of people live with severe water scarcity for at least one month of the year and humans use 70% of available fresh water for agricultural purposes, the monitoring of water irrigation systems is a recommended strategy to help conserve water (Green et al., 2018).…”
Section: Quality Of Food Resources In a Changing Climatementioning
confidence: 99%
“…Thus, certain phytochemicals relevant to health in crop plants may be positively influenced by environmental changes, while levels of some essential macro‐ and micro‐nutrients may be negatively affected. In view of the emerging research that suggests that certain environmental factors could negatively impact on the nutritional quality of food, the potential consequences for human health in the long‐term are concerning, particularly against the backdrop of the global scale of malnutrition, which includes protein‐energy, vitamin and mineral deficiencies (De Onis, Monteiro, Akré, & Glugston, 1993; Green et al., 2018; https://www.who.int/news-room/fact-sheets/detail/malnutrition). While biofortification could be one approach to mitigate the impact of climatic changes on food nutritional status (Green et al., 2018), more extensive scrutiny of the nutritional quality of crops, including NUS, in the context of predicted environmental challenges, should be aligned with other strategies for food security.…”
Section: Quality Of Food Resources In a Changing Climatementioning
confidence: 99%
“…Global food systems nowadays face many serious environmental challenges. How to overcome these environmental challenges of scarce water resources, decaying soil health, and climate change so as to feed and meet the nutritional needs of a growing population in the coming years is a primary task (Green et al, 2018). Sustainable sourcing practices undoubtedly play an increasing role in addressing the social and environmental challenges in the agricultural supply chains (Thorlakson, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…As atmospheric CO2 rises, plants are predicted to have increased starch and reduced protein content, which is associated with a decline in digestibility (Ziska, Epstein, & Schlesinger, 2009). Indeed, increased CO2 leads not only to decreased protein, but also reduced levels of iron and zinc in crops such as wheat, rice, potatoes, soy, and peas, and in fruits and vegetables, which are important sources of nutrients especially in many low-income countries (Fanzo, Davis, McLaren, & Choufani, 2018;Green et al, 2018). Conversely, some studies conclude that elevated CO2 levels can increase grain (including wheat and canola) yield, which is an important factor to support livelihoods.…”
Section: Adaptation In Nutritional and Chemical Traitsmentioning
confidence: 99%